Entropy‐Driven Carbon Dioxide Capture: The Role of High Salinity and Hydrophobic Monoethanolamine - Aleksa Petrović; Rodrigo Lima; Peter Westh; Ji‐Woong Lee (Advanced Energy & Sustainability Research)
Addressing atmospheric CO2 levels during the transition to carbon neutrality requires efficient CO2 capture methods. Aqueous amine scrubbing dominates large‐scale flue gas capture but is hampered by the energy‐intensive regeneration step, sorbent loss, and consequent environmental concerns with volatile amines. Herein, hydrophobic non‐volatile alkylated monoethanolamine (MEA) is introduced as a water‐lean CO2 absorbent in brine. The effects of alkylation of MEA, salinity, and aggregation of absorbents on the improved CO2 capture process are systematically investigated. The CO2 absorption facilitates spontaneous self‐aggregation of hydrophobic absorbents, which increases the entropy of water in high‐ion strength solutions. This effect is controlled by the salinity of aqueous solutions, affording comparative gravimetric CO2 uptake performance to benchmark MEA. It is experimentally verified that the hydrophobicity of alkylated MEAs in saline water is responsible for facile absorption, and also for mild regeneration conditions. Therefore, the entropy‐driven approach minimizes absorbent evaporation, corrosion, and decomposition, thus paving the way to realize energy‐efficient carbon capture.